The Effect of Electronic Word of Mouth (E-WOM), Influencer Marketing, and Halal Awareness on Consumer Buying Interest in Mountea Products - Fathurrohman, Muhammad Khaeru; Moh. Mukhsin; Isti Nuzulul Atiah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to determine whether Electronic Word Of Mouth (E-WOM), influencer marketing, and halal awareness partially or simultaneously have a positive and significant effect on consumer buying interest in Mountea products. This type of research uses quantitative research with a correlational approach. The sample in the study amounted to 83 respondents. Data analysis techniques are used for instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2) analysis with SPSS version 26.0. The results of the data analysis show that the results of the partial test (t test), Electronic Word Of Mouth (E-WOM) and influencer marketing partially have a positive and significant effect on consumer buying interest, while halal awareness has no significant effect. The simultaneous test results (F test) show that F count (43.474) > F table (2.72) with a significance value of 0.000 <0.05. It can be concluded that Electronic Word Of Mouth (E-WOM), influencer marketing, and halal awareness simultaneously have a positive and significant effect on consumer buying interest.